Selected articles by Len Kravitz and colleagues - Kravitz, L.
Vella, C. A. & Kravitz, L. (2004). Exercise After-Burn: A Research Update, IDEA Fitness Journal, 1(5), 42-47. Shedden, M. & Kravitz. L. Exercise and bone strength. IDEA Personal Trainer, 15(5), 34-37. Kravitz, L. (2004). The effect of concurrent training. IDEA Personal Trainer, 15(3), 34-37. Maes, J. & Kravitz, L. (2004). Training clients with arthrits. IDEA Personal Trainer, 15(2), 27-31. Shedden, M. & Kravitz. L. (2004). Exercise-induced Asthma. IDEA Personal Trainer, 15(1), 37-39. Vella, C. A., Kravitz, L. (2004). Staying cool when your body is hot. AKWA, January, 16-17. Maes, J.D. & Kravitz, L. (2003). Treating and preventing DOMS. IDEA Personal Trainer, 14(7), 41-45. Conn, C. A. & Kravitz, L. (2003). The remarkable calorie. IDEA Personal Trainer, 14(4), 28-35. Dalleck, L.C. & Kravitz, L. (2003). Optimize endurance training. IDEA Personal Trainer, 14(1), 37-42 Kravitz, L. (2002). Cellulite: Everything you want to know and more. Oxygen Magazine. Overturf, R. & Kravitz, L. (2002). Circuit vs. periodized resistance training for women. IDEA Personal Trainer, 13(10), 28-33. Vella C. & Kravitz, L. (2002). Gender differences in fat metabolism. IDEA Health and Fitness Source, 20(10), 36-46. Overturf, R. & Kravitz, L. (2002). Strength trainng and flexibility. IDEA Personal Trainer, 13(8), 17-19. Nelson, J. & Kravitz, L. (2002). Super slow resistance training. IDEA Personal Trainer, 13(6), 13-15. Kravitz, L. & Dalleck, L.C. (2002). Physiological factors limiting endurance exercise capacity. IDEA Health & Fitness Source, 20(4), 40-49. Vella, C. A., & Kravitz, L. (2002). Sarcopenia: The mystery of muscle loss. IDEA Personal Trainer,13(4), 30-35. Paez, C. J., & Kravitz, L. (2002). Exercise vs. diet in weight loss. IDEA Personal Trainer, 13(3), 15-17. Dalleck, L. C. & Kravitz, L. (2002). The history of fitness. IDEA Health and Fitness Source, 20(2), 26-33. Dalleck, L. C. & Kravitz, L. (2002). Sports conditioning and fatigue. IDEA Personal Trainer, 13(1), 28-33. Vella, C.H., Kravitz, L., & Janot, J.M. (2001). A review of the impact of exercise on cholesterol levels, IDEA Health and Fitness Source, 19(10), 48-54. Kravitz, L. (2001) Low-Back stability training, IDEA Personal Trainer, 12(9), 17-18. Physiology of Resistance Exercise Notes for Workshop Delegates Kravitz, L. (2001). Exercise and resting blood pressure, 16(7), 21-22. Janot, J. M. & Kravitz, L. (2001). Maximizing functional abilities in the older adult. IDEA Health and Fitness Source, 19(6), 38-45. Reynolds, J. M. & Kravitz, L. (2001). Resistance training and EPOC. IDEA Personal Trainer, 12(5), 17-19. Weingart, H. M., & Kravitz, L. (2001). Resistance training and bone mass. IDEA Personal Trainer, 12(3), 17,19-20. Marks, D. & Kravitz, L. (2001). Hormones and resistance Exercise. IDEA Personal Trainer, 12 (1), 19-20. Kravitz, L. (2000). Exercise and psychological health. IDEA Personal Trainer, 11(10), 19-21. Astorino, T., & Kravitz, L. (2000). Glycogen and resistance training. IDEA Personal Trainer, 11(7), 21-23. Street, R., & Kravitz, L. (2000). The ways to print and broadcast media: Your guide to good publicity. ACSM Health and Fitness Journal, 4, 7-11. Weingart, H. M., & Kravitz, L. (2000). Recent key studies. IDEA Personal Trainer, 11(6), 24-31. Janot, J., & Kravitz, L. (2000). Training clients with diabetes. IDEA Personal Trainer, 11(5), 15-17. Frankel, C.C, & Kravitz, L. (2000). The weight belt controversy. IDEA Personal Trainer, 11(3), 15-17. Frankel, C.C., & Kravitz, L. (2000). Periodization: State of the art training. IDEA Personal Trainer, 11(1), 15-16. Kravitz, L., Nowicki, K., & Kinzey, S.J. (1999). 1 RM Strength Testing. IDEA Personal Trainer, 10(9), 17,18. Kravitz, L., & Malone, R. (1999). Training for weight management. IDEA Personal Trainer, 10(7), 17, 18. Kravitz, L., & Kemerly, T. (1999). The impact of strength training on the back. IDEA Personal Trainer, 10, 14, 15. Kravitz, L., & Rockey, C. (1999). Career growth tips for the 21st century: A resource guide to career opportunities. ACSM Health and Fitness Journal, 3, 15-18. Kravitz, L. (1998). SuperAbs resource manual. Power of Excellence. 1, 1-20. NOTE: This hyperlink will take you to Len's University WEB Site. Kravitz, L. (1999). The good, bad, and ugly of home fitness equipment. Wellness Management, 15, 1, 10. Kravitz, L. (1999). Fight to be fit. ACE Fitnessmatters, 5, 6,7. Kravitz, L. (1998). Elliptical trainers go head-to-head. ACE Fitnessmatters, 4, 11,12, 15. Kravitz, L. (1997). Aerobic exercise vs. resistance training: Is this the battle of the fitness titans. IDEA Today, 15(6), 52-58. Kravitz, L., & Heyward, V.H. (1997). Fitness assessment part 4: Body composition. PERSONAL TRAINER, 8(5), 19-23 Mayo, J.J., & Kravitz, L. (1997). Fitness assessment part 3: Muscle strength and endurance. PERSONAL TRAINER, 8(4), 54-58, 60-62. Kravitz, L., & Mayo, J.J. (1997). The physiological effects of aquatic exercise: A brief review. Nokomis, Fl. Aquatic Exercise Association. Kravitz, L. (1996). Resistance training: Adaptations and health implications. IDEA Today, 14(9), 38-46. Kravitz, L. The age antidote. (1996). IDEA Today, 14(2), 28-35. Kravitz, L. (1996). The fitness professional's complete guide to circuits and intervals. IDEA Today, 14(1), 32-43. Kravitz, L., & Robergs, R. A. (1995). Is it genetic? IDEA Today, 13(4), 70-76. Kravitz, L. (1995). Exploring the mysteries of exercise. IDEA Today, 13(1), 48-55. Kravitz, L., & Heyward, V. (1995). Flexibility training. Fitness Management, 11(2), 32-33, 36-38 Kravitz, L., & Andrews, R. (1995). Fitness & the low back. IDEA Today, 13(4), 44-52. Kravitz, L. (1994). Understanding and enjoying research. IDEA Today, 12(9), 34-36. Robergs, R. A., & Kravitz, L. (1994). Making sense of calorie-burning claims. IDEA Today, 12(8), 27-32. Kravitz, L. (1994). The effects of music on exercise. IDEA Today, 12(9), 56-61. Kravitz, L., & Heyward, V. (1994). The exercise & cholesterol controversy. IDEA Today, 12(2), 38-42. Kravitz, L., & Robergs, R. A. (1993). To be active or not to be active. IDEA Today, 11(3), 46-53. Kravitz, L., & Heyward, V. (1992). Getting a grip on body composition. IDEA Today, 10(4), 34-39.